2008
DOI: 10.1371/journal.pone.0002389
|View full text |Cite
|
Sign up to set email alerts
|

Young Infants' Neural Processing of Objects Is Affected by Eye Gaze Direction and Emotional Expression

Abstract: Eye gaze is an important social cue which is used to determine another person's focus of attention and intention to communicate. In combination with a fearful facial expression eye gaze can also signal threat in the environment. The ability to detect and understand others' social signals is essential in order to avoid danger and enable social evaluation. It has been a matter of debate when infants are able to use gaze cues and emotional facial expressions in reference to external objects. Here we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 51 publications
2
62
1
Order By: Relevance
“…Taken together (see also review by Baldwin & Moses, 1996) these results provide strong evidence of early referential understanding of emotional expressions by the end of the first year of life. Furthermore, recent research appears to have identified differential brain responses to an object which has been the target of a fearful emotional expression by an adult in infants as young as 3 months of age (Hoehl, Wiese, & Striano, 2008). Although this does not imply that referential emotional understanding is in place at this age, it does indicate that referential cues related to emotion may bias object processing, which may be an early forerunner of this more sophisticated capacity.…”
Section: Social Referencingmentioning
confidence: 91%
“…Taken together (see also review by Baldwin & Moses, 1996) these results provide strong evidence of early referential understanding of emotional expressions by the end of the first year of life. Furthermore, recent research appears to have identified differential brain responses to an object which has been the target of a fearful emotional expression by an adult in infants as young as 3 months of age (Hoehl, Wiese, & Striano, 2008). Although this does not imply that referential emotional understanding is in place at this age, it does indicate that referential cues related to emotion may bias object processing, which may be an early forerunner of this more sophisticated capacity.…”
Section: Social Referencingmentioning
confidence: 91%
“…We tested this hypothesis in 3-, 6-and 9-month-old infants [Hoehl & Pauen, in preparation;Hoehl & Striano, 2010a;Hoehl, Wiese, et al, 2008]. Our initial hypothesis was that by the age of 6 months infants would show increased attention, as indicated by increased Nc amplitude, for objects that were gaze cued by a fearful face as compared to a neutral face.…”
Section: Referential Emotion Processing and Social Learningmentioning
confidence: 99%
“…Only recently have researchers begun to use neurophysiological measures and eye tracking to look more closely at how different emotional expressions are processed and how infants' attention towards objects is affected by emotional facial expressions [Hoehl, Wiese & Striano, 2008;Hunnius, de Wit, Vrins & von Hofsten, 2011]. Furthermore, individual differences regarding attentional biases towards facial expressions are now increasingly explored, which may provide information on later emotion regulation abilities and affective dysfunctions [Leppänen et al, 2011; see also Perez-Edgar, this vol.].…”
mentioning
confidence: 99%
“…As indicated in Hoehl's [2014] chapter, between five and seven months, infants not only preferentially look at fearful faces compared to happy faces; the event-related potential component associated with intense visual attention, negative central (Nc), shows increased amplitude to fearful faces relative to happy faces. In fact, as early as three months of age, babies had a stronger Nc response to the same object after a fearfulfaced person looked at it than they did to the same object after a neutral-faced person looked at it [Hoehl, Wiese, & Striano, 2008, cited in Hoehl, 2014.…”
Section: Reactions To Threatmentioning
confidence: 99%